CD49d marks Th1 and Tfh-like antigen-specific CD4+ T cells during Plasmodium chabaudi infection. (29th April 2021) - Jian, Jiun-Yu; Inoue, Shin-Ichi; Bayarsaikhan, Ganchimeg; Miyakoda, Mana; Kimura, Daisuke; Kimura, Kazumi; Nozaki, Eriko; Sakurai, Takuya; Fernandez-Ruiz, Daniel; Heath, William R; Yui, Katsuyuki
Abstract: Upon activation, specific CD4 + T cells up-regulate the expression of CD11a and CD49d, surrogate markers of pathogen-specific CD4 + T cells. However, using T-cell receptor transgenic mice specific for a Plasmodium antigen, termed PbT-II, we found that activated CD4 + T cells develop not only to CD11a hi CD49d hi cells, but also to CD11a hi CD49d lo cells during acute Plasmodium infection. CD49d hi PbT-II cells, localized in the red pulp of spleens, expressed transcription factor T-bet and produced IFN-γ, indicating that they were type 1 helper T (Th1)-type cells. In contrast, CD49d lo PbT-II cells resided in the white pulp/marginal zones and were a heterogeneous population, with approximately half of them expressing CXCR5 and a third expressing Bcl-6, a master regulator of follicular helper T (Tfh) cells. In adoptive transfer experiments, both CD49d hi and CD49d lo PbT-II cells differentiated into CD49d hi Th1-type cells after stimulation with antigen-pulsed dendritic cells, while CD49d hi and CD49d lo phenotypes were generally maintained in mice infected with Plasmodium chabaudi . These results suggest that CD49d is expressed on Th1-type Plasmodium -specific CD4 + T cells, which are localized in the red pulp of the spleen, and can be used as a marker of antigen-specific Th1 CD4 + T cells, rather than that of all pathogen-specific CD4 + T cells. Abstract : CD49d is a marker for antigen-specific Th1 cells in malaria